Immunization of calves against enterotoxigenic colibacillosis by vaccinating dams with purified K99 antigen and whole cell bacterins. - Acres, S D (1979)
Pregnant cattle were either vaccinated subcutaneously with (i) a suspension of purified Escherichia coli K99 pili, (ii) a Formalin-killed whole cell bacterin containing enterotoxigenic E. coli strain B44 (O9:K30;K99:H-), or (iii) a bacterin containing six different strains of bovine enterotoxigenic E. coli (multiple-strain bacterin), or were left as nonvaccinated controls. After birth, calves were allowed to nurse their dams and, at 12 to 14 h of age, were challenged orally with 10(11) cells of enterotoxigenic E. coli strain B44. Colostral antibody titers were determined against K99, K30, and O9 antigens of B44. In the nonvaccinated control group, 9 of 10 calves developed diarrhea and died within 24 to 72 h. Similarly, all six calves in the multiple-strain bacterin group developed diarrhea and four died. In contrast to calves in the two groups mentioned above, calves nursing cows vaccinated with either purified K99 or the homologous whole cell bacterin were protected against fatal diarrhea. There was a highly significant correlation (P less than 0.0005) between protection against fatal diarrhea and K99, but not K30 or O9 colostral antibody titers. Vaccination of cows with either purified pili or whole cell preparations containing sufficient K99 antigen may provide a means of preventing enterotoxigenic colibacillosis in calves.